2003
DOI: 10.1111/j.1445-5994.2003.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of primary hyperparathyroidism: controversies, practical issues and the need for Australian guidelines

Abstract: Primary hyperparathyroidism (PHPT) is one of the most common endocrine disease processes, however the clinical presentation in 2003 is typically characterized by minimal signs or symptoms of hypercalcaemia or para-thyroid hormone (PTH) excess. Recent developments in imaging and management of PHPT have been published, however the area of biochemical investigation has been relatively neglected. A group of experts convened in April 2002 to consider whether changes were needed to the 1990 consensus guidelines whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
0
29
1
Order By: Relevance
“…The patients with PHPT included in the study (15 women and 9 men) were recruited from the Department of Surgery at the Hospital MarthaMaria in Munich, Germany. The inclusion criteria for the PHPT group comprised an increased total serum concentration of calcium (Ͼ2.65 mmol/l), an inappropriately high serum level of PTH (Ͼ67 pg/ml), serum creatinine Ͻ1.3 mg/dl, postoperative normalization of serum calcium, and sonographic and histological confirmation of parathyroid adenoma (3,10). The mean age of the patients was 58.7 Ϯ 17.3 yr (range 26 -80 yr), and their mean total serum calcium concentration was 2.88 Ϯ 0.04 mmol/l before parathyroid surgery.…”
Section: Patientsmentioning
confidence: 99%
“…The patients with PHPT included in the study (15 women and 9 men) were recruited from the Department of Surgery at the Hospital MarthaMaria in Munich, Germany. The inclusion criteria for the PHPT group comprised an increased total serum concentration of calcium (Ͼ2.65 mmol/l), an inappropriately high serum level of PTH (Ͼ67 pg/ml), serum creatinine Ͻ1.3 mg/dl, postoperative normalization of serum calcium, and sonographic and histological confirmation of parathyroid adenoma (3,10). The mean age of the patients was 58.7 Ϯ 17.3 yr (range 26 -80 yr), and their mean total serum calcium concentration was 2.88 Ϯ 0.04 mmol/l before parathyroid surgery.…”
Section: Patientsmentioning
confidence: 99%
“…Vitamin D metabolism has been explored only in a small number of FHH patients (17)(18)(19). We have recently reported on the ability of the calcium/creatinine clearance ratio (CCCR) and other variables of renal calcium excretion to discriminate between FHH and PHPT (20), as described by Marx et al and others (1,(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…1,6,26 However, in the present study, an elevated incidence of musculoskeletal manifestations was observed; more than half of the patients had signs/symptoms of osteoarthritis, one third had diffuse arthralgia, followed by symptoms of fibromyalgia, chondrocalcinosis, and tendinopathies.…”
Section: Discussionmentioning
confidence: 41%
“…5 Less frequently, an increase in the size of two glands, or even diffuse hyperplasia, 5 is seen, and parathyroid carcinoma is a rare disorder. 4 The majority of the patients have a subtle increase in PTH and calcium levels and they are asymptomatic; 6 consequently, the history and physical exam rarely provide any indications of PHP. In less than half of the cases, PHP can present with different clinical manifestations secondary to hypercalcemia.…”
Section: Introductionmentioning
confidence: 99%